Estratégias de suplementação para recria e terminação de tourinhos a pasto na transição água-secas e secas - Freiria, Lucien Bissi da (2019)
Three experiments were available supplementation strategies in the growth and finishing phase of beef cattle at pasture. In experiment 1, we hypothesized that a decrease flint corn particle size in supplements of young bulls in grazing promotes a better use of starch by animals, with a subsequent increase in animal performance. This experiment aimed to evaluate supplements with different ground corn particle size on growth performance, intake and the apparent digestibility of the nutrients for beef cattle at pastures during the rainy-dry transition season. Sixty-four Nelore bulls, with an average age of 16 months and 303.6±18.0 kg of body weight (BW) were distributed in a completely randomized design. The treatments were: WG = whole grain (geometric mean particle size, dgw, 6,262 µm); CG = coarse ground grain (dgw, 2,882 µm); MG = medium ground grain (dgw, 1,011 µm); FG = fine ground grain (dgw, 0,621 µm). There were not differences (P>0.05) for intake and digestible of dry matter (DM), forage, organic matter (OM), crude protein (CP), neutral detergent fiber corrected for ash and protein (NDFap), and total digestible nutrient (TDN). The starch digestion total tract was higher (P<0.05) with grinding corn grain compared whole corn grain, but did not observed between grindings (P>0.05). The starch fecal concentration decreases with grinding corn grain compared whole corn grain (P<0.05). However, did not observed differences between treatments for growth performance (P>0.05). The supplementation with CG promoted slightly greater net revenue (+2.7%) and return for ha (+3.9%) comparing with WG, while, MG and FG have worse economic results. Therefore, the grinding grain corn of supplement improve efficiency utilization of starch with less in feces, but not improve product performance and nutrient digestibility, while, for economic performance showed major return with use of coarse ground grain in supplements for young bulls in grazing. In experiment 2, the aim of use fat supply source (free oil and rumen-protected) on nutrient intake and digestibility for beef cattle at pasture. Five rumen-cannulated Nelore bulls, with an average age of 26 months and 467,8±32.8 kg of body weight (BW) were distributed in a Latin square design 5 x 5(five treatments × five experimental periods). The treatments were: WF without fat, PS protected fat soybean oil, PA protected fat palm oil, SO soybean free oil, CO corn free oil. They were analyzed nutrients intake and digestibility, ruminal pH and NH3-N, serum urea, and efficiency of N utilization. There were no differences (P>0.05) for intake and digestible of: dry matter (DM), forage, organic matter (OM), crude protein (CP), neutral digestibility fiber (NDF), neutral digestibility corrected ash and protein (NDFap), nonfiber carbohydrates (NFC) and total digestible nutrient (TDN), except EE, there was an increase of (P<0.05) intake and digestibility with the inclusion of fat supply. The ruminal pH and NH3-N, serum urea, and efficiency of N utilization, did not affect (P>0.05) independent supplementation. The supplementation of 2 g/kg BW with inclusion low-level free oil (130 g/kg DM supplement) or rumen-protected fat (160 g/kg DM supplement) for beef cattle at pasture was not interfere in the characteristic nutrient intake and digestible. In experiment 3, we tested the hypothesis that increase supplementation levels associate inclusion of soybean hulls is a strategy that could be used to replacement forage intake, with increase nutrient digestibility (DM and NDF), resulting increase dry matter intake, of beef cattle at pasture in the dry season. Five Nellore bulls (499.0±19.7 kg of body weight) were used in a 5 × 5 Latin square design with five supplements and five experimental periods of 17 days. The treatments were mineral supplement (ad libitum, CONTROL-), mineral supplement + urea (CONTROL+), protein-energy supplement intake 900 g/day (SPE900), 1,800 g/day (SPE1800) and 2,700 g/day (SPE2700), available of intake and digestible nutrient, and the ruminal pH and NH3-N (ammonia nitrogen). Supplemented animals (SPE900, SPE1800 and SPE2700) showed lower (P < 0.05) intake of forage comparing with CONTROL- or CONTROL+, and linear reduces (P < 0.05) forage intake for SPE900 to SPE2700. However, the supplementation is not promoting change of intake and digestibility nutrients, although, the protein intake increasing for CONTROL+, SPE900, SPE1800 and SPE2700 in relation CONTROL+. On another hand, that ruminal pH and NH3-N was similar in all treatments. Higher supplementation level associate inclusion soybean hull for beef cattle at pasture in the dry season not influence dry matter intake, nutrient digestibility and ruminal parameters, but reduce forage intake. It’s shown potential use of soybean hull in supplements as possibility factor to increase of number the grazing animal for area, due reduction dependent of forage intake.